A Urokinase Receptor-Bim Signaling Axis Emerges During EGFR Inhibitor Resistance in Mutant EGFR Glioblastoma - Wykosky, Jill (Cancer Res, 2014)
EGFR is the most common genetically altered oncogene in glioblastoma (GBM), but small molecule EGFR tyrosine kinase inhibitors (TKIs) have failed to yield durable clinical benefit. Here we show that in two novel model systems of acquired resistance to EGFR TKIs, elevated expression of urokinase plasminogen activator (uPA) drives signaling through the MAPK pathway, which results in suppression of the pro-apoptotic BCL2-family member protein BIM (BCL2L11). In patient-derived GBM cells and genetic GBM models uPA is shown to suppress BIM levels through ERK1/2 phosphorylation, which can be reversed by siRNA mediated knockdown of uPA. TKI-resistant GBMs are re-sensitized to EGFR TKIs by pharmacological inhibition of MEK or a BH3 mimetic drug to replace BIM function. A link between the uPA-uPAR-ERK1/2 pathway and BIM has not been previously demonstrated in GBM, and involvement of this signaling axis in resistance provides rationale for a new strategy to target EGFR TKI-resistant GBM.